EFEKTIVITAS PROGRAM PELAYANAN ONLINE KEPENDUDUKAN DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK (Studi Kasus Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Gresik) - Izzatul Hasibah; Hayat; Hirshi Anadza (Halu Oleo University, 2022)
The purpose of this study is to determine the effectiveness of the Poedak application program that has been running so far. The research method used in this study is descriptive qualitative by describing phenomena or events that occur in the field. The research focus is related to the effectiveness of the Poedak application program using Budiani's theory (program objectives, program outreach, program objectives, and program monitoring) and the implementation of services using the Poedak application, including the supporting and supporting factors. Data collection was carried out using observation techniques, interviews, document collection, and visual documentation materials. The results obtained in the study showed that the Poedak application program was running quite effectively based on the indicators used by the researchers. However, there are several achievements that have not been maximized. There are several points that need to be improved so that it can be said to be optimal. As in the socialization of the program that is carried out less optimally. Through the research process carried out, several suggestions were found that researchers could provide, namely by optimizing the socialization of the Poedak application program to the public, adding information on the official Disdukcapil website about the Poedak application program, and clarifying procedures and administrative rules related to filing services online.